A Third Way?: Vietnamese Catholics and French Personalism from Colonialism to Early Independence - O’Mahony, Jerome (International journal of Asian christianity, 2024)
This article seeks to engage with the particular historical moment when, despite the cold war dichotomy of communism and capitalism, the short-lived (Southern) Republic of Vietnam under its first president, the Catholic, Ngô Đình Diệm (1901–1963) attempted to tread a third way. Diệm sought to introduce a Vietnamised form of French Catholic Emmanuel Mounier’s (1905–1950) political philosophy, Personalism, into the ideological framework of the new Republic, building upon an earlier exchange between Vietnamese and French Catholics. Ultimately this was unsuccessful and Personalism was unable to unify South Vietnam’s diverse society in opposition to the communist North, culminating in the ousting and assassination of Diệm in 1963. This moment offers a glimpse of a different path, suggesting that global capitalist liberal order might not be the only future. This article brings together various sources on Personalism and Vietnam to depict this historical moment.